From Curlers to Chainsaws Women and Their Machines - Dyer, Joyce; Cognard-Black, Jennifer; MacLeod Walls, Elizabeth (Michigan State University Press, 2016)
The twenty-three distinguished writers included in From Curlers to Chainsaws: Women and Their Machines invite machines into their lives and onto the page. In every room and landscape these writers occupy, gadgets that both stir and stymie may be found: a Singer sewing machine, a stove, a gun, a vibrator, a prosthetic limb, a tractor, a Dodge Dart, a microphone, a smartphone, a stapler, a No. 1 pencil and, of course, a curling iron and a chainsaw. From Curlers to Chainsaws is a groundbreaking collection of lyrical and illuminating essays about the serious, silly, seductive, and sometimes sorrowful relationships between women and their machines. This collection explores in depth objects we sometimes take for granted, focusing not only on their functions but also on their powers to inform identity. For each writer, the device moves beyond the functional to become a symbolic extension of the writer's own mind-altering and deepening each woman's concept of herself.